Physico-chemical characterization of nano-emulsions in cosmetic matrix enriched on omega-3 - Kabri, Tin-hinan (BioMed Central, 2011)
BACKGROUND: Nano-emulsions, as non-equilibrium systems, present characteristics and properties which depend not only on composition but also on their method of preparation. To obtain better penetration, nanocosmeceuticals use nano-sized systems for the delivery of active ingredients to targeted cells. In this work, nano-emulsions composed of miglyol, rapeseed oil and salmon oil were developed as a cosmetic matrix. Measurements of different physico-chemical properties of nano-emulsions were taken according to size, electrophoretic mobility, conductivity, viscosity, turbidity, cristallization and melting point. The RHLB was calculated for each formulation in order to achieve maximum stability. RESULTS: Both tween 80 and soya lecithin were found to stabilize formulations. The results showed that rapeseed oil and miglyol are the predominant parameters for determining the expression of results concerning the characterization of emulsion. Based on the mixture design, we achieved the optimal point using the following formulation: 56.5% rapessed oil, 35.5% miglyol, and 8% salmon oil. We considered this formulation to be the best as a nanocosmeceutical product due to the small size, good turbidity, and average HLB. CONCLUSIONS: This study demonstrates the influence of formulation on the physico-chemical properties of each nano-emulsion obtained by the mixture design.